The influence of using visual and auditory activities in the E.F.L. Learning in beginner students in a public School in Bogotá - Rodriguez Rayo, Marfa Rocio (Corporación Universitaria Minuto de Dios, 2015)
This research project is focused in identifying the influence of the use of visual and auditory activities in the learning process in beginner students from a public school in Bogotá. Thirty students with an average of ten to thirteen years old were participating in the project during six weeks. Outcomes, students’ journals, field notes and observations by teacher researcher to students participating were the data collections to obtain information. Data analysis revealed that the incorporation of visual and auditory activities made easier the learning process motivating students to participate on the lessons improving their English knowledge easier and faster. Besides students demonstrated their attitudes and performance towards the English class through meaningful and attractive activities that promoted a different and better environment where students enjoyed doing through several games, songs and various resources that made easier the foreign language learning.
Keywords: Aprendizaje; Escuelas públicas; Educación; MÉTODOS DE ENSEÑANZA; APRENDIZAJE; ESCUELAS PÚBLICAS